Potential of dual-use policies to meet family planning and HIV prevention needs: a case study of Zimbabwe and Mozambique. Issue 4 (1st October 2008) - Prata, Ndola; Sreenivas, Amita; Bellows, Ben
Abstract : Background and methodology: The fight against the HIV epidemic in many high-prevalence countries is a struggle to motivate culturally relevant risk reduction in general populations that have been educated to associate HIV risk with commercial sex, injection drug use and other stigmatised behaviours. Common concurrent partnerships, which facilitate transmission of HIV in many high-prevalence countries, are only beginning to receive the attention they deserve. This has made the promotion of dual-use methods, such as condoms, for individuals who require both HIV protection and contraception very difficult. Recent research on concurrent partnerships and the implications for high HIV risk in sexually networked but sexually modest general populations is forcing another assessment of the response to HIV. In the light of the epidemic, it is important to better understand which policies will better meet HIV prevention and family planning (FP) needs. This article explores the potential of dual-use policies by examining Zimbabwe and Mozambique. Results: Zimbabwe, with a vertically driven, stronger FP programme predating the HIV epidemic, has not yet seen an increase in condom use to the level desired by their moderately strong HIV prevention programme – one that has adopted a primarily single-use condom policy. Mozambique, however, continues to have a much weaker FP programme, but is witnessing a significant increase in condom use driven by their strong HIV programme – one that is further integrated with FP content. Discussion: Integration of HIV and FP programmes has the potential to meet the need for HIV and pregnancy prevention more efficiently. By themselves, these programmes are unable to meet the need for condoms. The poorest of the poor are feeling the brunt of this inadequacy. Countries such as Zimbabwe and Mozambique have the potential to tremendously improve their efforts in increasing condom use. We suggest that thoughtful and detailed integration of HIV and FP programmes will work synergistically to reach common goals. Until a more promising method besides condoms is commercially available for protection against unintended pregnancy and sexually transmitted infections such as HIV, effective strategies must include dual-use policies as well as counselling on all available contraceptive methods so that women can maximise the benefits of mixing methods.